The Phenomenon of Bamboo Music Buskers in Semarang: An Urban Music Perspective - Sunarto, Sunarto; Sejati, Irfanda Rizki Harmono; Haryono, Slamet; Susetyo, Bagus (Resital: Jurnal Seni Pertunjukan, 2024)
This study aims to explore the phenomenon of bamboo music buskers in Semarang from an urban music perspective, focusing on their role in the city's cultural landscape and the dynamics of social interactions in public spaces. The methodology used in this study is a qualitative approach with participatory observation techniques, in-depth interviews with buskers, and documentation analysis. Data collection was conducted in several strategic locations in Semarang, such as the town square, markets, and other crowded centers. The results of the study indicate that bamboo music buskers play a significant role in enriching the color of urban music in Semarang. They not only function as street entertainers, but also as cultural agents who introduce and preserve traditional music in a modern context. Bamboo music, with its unique and organic characteristics, attracts the attention of people from various circles and often creates warmer social interactions between buskers and their listeners. In addition, this study found that bamboo music buskers face challenges in the form of social stigma and government regulations that are less supportive of their activities in public spaces. The implications of this study indicate that bamboo music buskers have the potential to be developed as a city cultural asset that can support local tourism and strengthen Semarang's cultural identity. In addition, this study recommends the need for more inclusive policies and support for the sustainability of urban music rooted in local traditions, so that it can create more dynamic and culturally diverse public spaces.